Images of a Dana: Coverage on Spanish Television Analysis of the Programming for October 29, 2024 - Erviti Ilundáin, María Carmen (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This study examines the television coverage of the DANA on October 29, 2024, in Spain, focusing on the extent and quality of news reporting and the use of images. The DANA, an extreme meteorological phenomenon, severely impacted the Valencian Community, causing over 200 deaths and extensive economic losses. While morning programs alerted viewers to the impending risk, prime-time coverage was limited, except for Código 10 on Cuatro. Most broadcast images came from eyewitnesses rather than reporters. The study concludes with recommendations on image verification, ethical standards, and programming adjustments for improved emergency coverage.